Involvement of Restored Treg Cells in the Immune Pathogenesis of Parkinson’s Disease (PD) Running Title: Immune Pathogenesis of Parkinson’s Disease (American Journal of Medical Science and Innovation, 2024)
Neural regression with neuroinflammation and immune dysfunction through neuro-degradative disorder is known as Parkinson’s disease (PD). Parkinson’s disease is a progressive degradative neuronal disorder. In this disease, the continuous depletion of dopaminergic neurons and the existence of protein Lewy bodies are the key points of PD development. In PD patients, regulatory T cells (Tregs) are decreased in number and have an impaired proliferative capacity that affects the suppression of T-cell characteristics. The thymus involution decline in the functionality of T-cell development and consequently naïve T cells makes the immune system more vulnerable to losing its immune surveillance, increasing morbidity and mortality in aged individuals. The persistent process of thymic involution with age vigorously contributes to a progressive reduction in thymic output. Genomic damage, cellular senescence, and epigenetic alterations are the hallmarks of cellular or molecular damage in aging. Therapeutic potential for regeneration of the thymus would improve immunity. Some strategies and approaches have focused on cell-based approaches, technology based on organoid and scaffold modulating of endogenous and exogenous compounds to help in the thymus regeneration, and fabrication technologies that could be used as regenerative approaches. Last but not least the pluripotent stem cell therapies.